Campylotropis albopubescens stat. nov. (Leguminosae: Papilionoideae: Desmodieae): the only species in the genus reproduced via rootstocks - Liao, Min; Xu, Bo (Phytotaxa, 2020)
Campylotropis pinetorum is a widespread and morphologically varied species including three subspecies: subsp. pinetorum, subsp. velutina, and subsp. albopubescens. However, our recent extensive observations indicated that C. pinetorum subsp. albopubescens, the only taxon in the genus that can form dominant communities via rootstocks, is clearly distinguished from subsp. pinetorum and subsp. velutina due to its distinct morphological characters: ovate to ovate-triangular stipules; branches, inflorescence rachises, calyces, and both surfaces of leaflets densely white pubescent; longer and wider bracts; purplish-red flowers; standard without green spots; pods without net veins; and presence of both sexual and vegetative reproduction types. Therefore, C. pinetorum var. albopubescens, the basionym of C. pinetorum subsp. albopubescens, is elevated to the species rank as C. albopubscens (Iokawa & H.Ohashi) M.Liao & B.Xu, stat. nov.